Investigation of the effects of an 8-week cross-country skiing exercise program on various reaction time parameters, selective attention and academic achievement in adolescents - Musab Çağın; Sezen Çimen Polat; Halil Sarol; Amador García Ramos; Abdulkerim Çeviker (BMC, 2024)
Abstract Exercise slows or helps reverse the shrinkage of key cognitive brain regions such as the hippocampus, which is important for information processing, learning, reasoning and planning. For this reason, it is thought that regular exercise of individuals, especially during adolescence, which is considered one of the most important processes of development, can increase their performance in areas where cognitive activities are at the forefront. Cross-country skiing, one of the leading branches of winter sports, has a much more complex structure, unlike the branches that are widely preferred today (football, basketball, volleyball, etc.) and is a branch where many motor skills are exhibited at the same time For this reason, the effect of cross-country skiing, which is defined as more complex and difficult in terms of biomotor than other branches, on cognitive activities is a matter of curiosity. Therefore, the aim of the research is; to examine the cognitive effects of cross-country skiing exercise. The study involved 54 (26 male, 28 female) adolescents who had no prior experience in any licensed sports. The average age of the participants was determined as 12.61 ± 1.32. The participants were divided in experimental and control groups. Reaction performances were determined using the ÇAĞIN Hand and Foot Reaction Tests, selective attention performances were evaluated using the Flanker Test and academic achievement was determined using the e-Okul system. Two-way ANOVA revealed significant group × time interactions for hand and foot simple, selective, discriminative reaction time, selective attention and academic achievement (p < 0.05) due to improved values at post-test for the experimental group but not for the control groups. No significant group × time interactions were observed for correct reaction rate for all reaction parameters (p > 0.05). The study concludes that the cross-country skiing exercise, which was applied to adolescents for eight weeks, had a positive impact on the parameters of reaction, selective attention and academic achievement. Therefore, parents are suggested to encourage their children to exercise and engage in sports practices like cross-country skiing to improve cognitive and academic performance during adolescence.